(untitled) (Conferences, 2026)
The present research focused on the research trends in artificial intelligence and Self-regulation, educational technology and generative artificial intelligence are included in the emerging or declining themes. This study explores the concepts of self-regulation and AI through a bibliometric analysis of relevant literature sourced from Scopus during the period 2021 to 2026 March. Data were gathered through a bibliometric analysis of 211 documents using Biblioshiny and bibliometric methods. Non-Western countries like China, India, and South Korea are also dominating the research field, indicating a shift from Western to Eastern countries.